Analysis of Marketing Strategy on Marketing Effectiveness at Yomart Retail Stores in Majalengka Regency - Vida Haifa Khoerunnisa (Jurnal Manajemen Bisnis dan Pariwisata, 2025)
This study aimed to analyze the marketing strategies implemented by Yomart retail stores in Majalengka Regency and evaluate their effectiveness in supporting marketing performance. The research addressed key components of the marketing mix, including product, price, place, and promotion. A descriptive quantitative method was employed by distributing questionnaires to 40 Yomart consumers. The data collected were processed using validity testing, reliability testing, and multiple regression analysis to determine the influence of marketing strategy variables on consumer responses. The findings indicated that Yomart’s marketing strategy had been effectively implemented, particularly in terms of product completeness and competitive pricing, which contributed significantly to consumer satisfaction and purchasing decisions. Promotional activities, especially short-term programs, also demonstrated a positive impact on increasing consumer interest. However, the study identified the need to strengthen customer loyalty initiatives and expand digital promotional efforts to enhance market reach. Overall, the research concluded that Yomart’s marketing strategy had effectively supported retail performance, while also providing practical insights for improving future strategic planning and sustaining competitiveness in the retail industry.